Climatology of medium-scale traveling ionospheric disturbances observed by a GPS network in central China - Ding, Feng; Wan, Weixing; Xu, Guirong; Yu, Tao; Yang, Guanglin; Wang, Jing-song (Journal of Geophysical Research: Space Physics, 2011)
The 15‐month climatology of medium‐scale traveling ionospheric disturbances (MSTIDs) during a solar minimum period has been constructed from observations of a dense GPS receiver array in Central China. In total, 793 MSTID events are identified, with peaks in occurrence at 1500 LT and 0100 LT. The occurrence of MSTIDs decreases following an increase in geomagnetic activity, with 46% of the MSTIDS occurring in the daytime. Daytime MSTIDs are characterized by a major occurrence maximum around the winter solstice and by an equatorward propagation direction. The period, phase velocity, azimuth, and amplitude of daytime MSTIDs are 20–60 min, 100–400 m/s, 130°–270°, and 0.8–1.5%, respectively. The remaining 54% of the MSTIDs occurred at night, and were characterized by a peak in occurrence at the summer solstice and by a southwestward propagation direction. The period, phase velocity, azimuth, and amplitude of nighttime MSTIDs are 20–70 min, 50–230 m/s, 170°–300°, and 2–7%, respectively. The propagation directions and the seasonal behaviors support the view that daytime MSTIDs are an ionospheric manifestation of atmospheric gravity waves from the lower atmosphere, while a possible excitation mechanism of nighttime MSTIDs is the electrodynamics process caused by plasma instability in the F layer. Key Points Daytime MSTIDs have a peak at winter solstice and propagated southward Nighttime MSTIDs have a peak at summer solstice and a southwestward direction Comparing with HF Doppler observation, we find a height dependence of MSTIDs